Reirradiation: Evaluation of the occurrence and type in cancer treatment for lung – 2024 - Catherine Laferlita; Yiota Nicolaou; Katrina Woodford; Nicholas Hardcastle; Susan Harden; Kenton Thompson (Technical Innovations & Patient Support in Radiation Oncology)
With advancements in oncology practice, patients are living longer and returning for repeat courses of radiotherapy. Reirradiation (ReRT) is becoming a viable treatment option for patients. This single-institution, retrospective audit evaluates the number of patients with primary lung cancers who underwent radical retreatment to the thorax in 2024 and categorises them according to the European Society for Radiotherapy and Oncology (ESTRO) and European Organisation for Research and Treatment of Cancer (EORTC) consensus definition. Of the 511 patients with primary lung cancer in our institution who returned for further radiotherapy in 2024, 42 received radical retreatment to the thorax. Inconsistencies were seen in documentation across patient information platforms in relation to cumulative dose assessment and minimal documentation of radiobiological considerations such as equivalent dose in 2 Gy fraction (EQD2) were discovered. As a result of this study, recommendations were made to improve current practice.